The Impact Of Financial Literacy, Financial Inclusion And Technology On Increasing Msme Profits (Depok City Case Study) - Kery Utami; Raden Parianom; Hani Novanti (UNIVED Press, 2025)
The rapid growth of MSMEs in Indonesia provides great opportunities for the national economy. However, to increase the competitiveness and sustainability of MSMEs, a deeper understanding of the factors that influence their performance is needed. This research specifically focuses on the role of financial literacy, financial inclusion and financial technology in driving MSME profit growth in Depok City. Apart from that, this research also considers gender roles as a differentiating factor. This research uses a quantitative approach by collecting data through questionnaires distributed to 100 MSMEs in Depok City who have utilized financial technology. The data obtained was then analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The results of the analysis show that financial literacy, financial inclusion and financial technology have a positive and significant influence on MSME profit growth. These findings indicate that increasing financial literacy, expanding access to financial services, and utilizing financial technology are strategic steps to improve the performance of MSMEs. Although gender is not proven to moderate the relationship between independent variables and profit growth, this research provides an important contribution in developing policies to support the growth of MSMEs in Indonesia. The results of this research can be a basis for governments, financial institutions, and other stakeholders to design more effective programs in increasing financial literacy, expanding financial inclusion, and encouraging the adoption of financial technology among MSMEs.